Altered functional connectivity in first-episode and recurrent depression: A resting-state functional magnetic resonance imaging study - Sun, Jifei; Du, Zhongming; Ma, Yue; Chen, Limei; Wang, Zhi; Guo, Chunlei; Luo, Yi; Gao, Deqiang; Hong, Yang; Zhang, Lei; Han, Ming; Cao, Jiudong; et al. (Frontiers in Neurology, 2022)
Background:Previous fMRI studies are scarce on the differences in functional activity of brain networks between first depressive episode (FDE) and recurrent depressive episode (RDE). The present study observes and compares the altered functional connectivity (FC) characteristics in default mode network(DMN), cognitive control network(CCN) and affective network(AN) between RDE and FDE, and further investigates the correlation between abnormal FC and clinical symptoms. Methods: This study recruited 30 patients with RDE, 30 patients with FDE and 30 healthy controls (HCs). All subjects underwent the resting-state functional magnetic resonance imaging. The seed-based FC method was used to analyze the abnormal brain network of DMN, CCN and AN in three groups, and further explore the correlation between abnormal FC and clinical symptoms. Results:ANOVA showed significant differences in FC of DMN, CCN, AN between the three groups in the frontal, parietal, temporal and precuneus lobes and cerebellum. Compared with the RDE group, the FDE group generally showed lower FC in DMN, CCN, AN. Compared with the HC group, the FDE group had lower FC in DMN, CCN, AN, while the RDE group only had lower FC in DMN, AN. Moreover, FC in the left posterior cingulate cortices and right inferior temporal gyrus in the RDE group were positively correlated with the 17-item Hamilton Rating Scale for Depression (HAMD-17), and FC in the left dorsolateral prefrontal cortices and right precuneus in the FDE group were negatively correlated with the HAMD-17. Conclusions:Both of RDE and FDE groups showed multiple abnormal brain network FC alterations, however, the alterations of abnormal FC were featured more extensive and intensive in the FDE group.